Study of Indonesia's participation in ICSID - Agus Saiful Abid (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Indonesia has ratified the International Convention Centre For Settlemen Of Investment Disputes (ICSID) with the enactment of Law No. 5 of 1968 concerning settlement of disputes between Countries with foreign Citizen on Investment on June 29, 1968. The purpose of the ratification of the ICSID Convention is to encourage and foster foreign investment in Indonesia as well as provide legal certainty to the settlement of disputes between governments and foreign investors. Until now there are some cases in which the Indonesian government in dispute with foreign investors includeAmco, Kaltim Prima Coal. (KPC), Asia Camex Holding and Churchill Mining Plc. After decades of economic growth in Indonesia into the top 5 of the world economy as well as the Law No. 30 of 1999 on Arbitration, becomes interesting when reviewing and analyzing the participation of Indonesia in the ICSID, so attractive when assessing why Indonesia participated in the ICSID Convention? How profits were and damages Indonesia joined the ICSID? And how the government should adopt the attitude of Indonesia as a member of the ICSID fore? The method used is a normative juridical by studying the principles of the law derived from the materials library. Specifications research is descriptive analytical. The data used are secondary data consists of primary legal materials, secondary law and tertiary legal materials. The data was then analyzed qualitatively and the results outlined in report form. Keywords: Analysis, Indonesia, ICSID.